ANALISIS GAYA BAHASA DAN MAKNA LIRIK LAGU DALAM ALBUM MERA LIDA - Asraini, Asraini; Candrasari, Ratri; Mahsa, Masithah; Sari, Dewi Kumala (FISIP Universitas Malikussaleh, 2025)
This research aims to describe the language style and meaning in the lyrics of the song on the album Mera Lida. This type of research is qualitative descriptive. The source of research data is 11 songs. The research data is in the form of words, phrases, sentences and verses. The research technique uses the techniques of reading, listening, and taking notes. The results of this study are: 1) The language styles found are; (1) comparative language styles include; metaphors, personifications, and antithesis. (2) The style of opposing language includes; hyperbole, litots, paradoxes, and sarcasm. (3) The style of the language of association includes; synecdoke, alusio, and euphymism. (4) Repetitive language styles include; assonance, anaphora, and epistrophae. The data in the study is marked by word markers, phrases, sentences, and stanzas. 2) The meaning of the lyrics of the Mera Lida album includes; (1) metaphorical comparative language styles, including; The metaphor is marked